The Effect of Dietary Synbiotics in Actively Racing Standardbred Horses Receiving Trimethoprim/Sulfadiazine - Maria Lagounova; Jennifer L. MacNicol; J. Scott Weese; Wendy Pearson (Animals, 2023)
Synbiotics are often provided to horses receiving antibiotics to protect against microbiome disturbances, despite a lack of evidence for efficacy. The purpose of this study was to evaluate the effect of a synbiotic product in horses receiving antibiotics. Sixteen actively racing Standardbred horses were randomly allocated (four-way crossover) to one of four groups: antibiotics (10 days; AB), synbiotics (28 days; PROBIOPlusTM; PBP), PBP + AB, or Control. The fecal microbiome was investigated using 16S rRNA sequencing, and fecal dry matter (DM; %), pH, and scores (FS; 0–9) were measured. Data were analyzed with two-way ANOVA. Results found microbiota differences in community membership between PBP + AB and all other treatments during and after antibiotic treatment. During antibiotic treatment, AB and PBP + AB were significantly different from Control. After antibiotic treatment, PBP + AB was significantly different from all other treatments. The few differences found in relative abundance of phyla or predominant genera were mostly in fiber degrading bacteria. The Fibrobacter population was significantly higher in AB and PBP + AB horses than Control. Unclassified Ruminococcaceae was significantly higher in Control than AB and PBP. After antibiotic treatment, PBP + AB horses were significantly higher than PBP horses. In conclusion, these data provide support for the ability of PROBIOPlus™ to maintain healthy gastrointestinal microbiome during antibiotic treatment.